Technological Skills of Differential Calculus in High School (Docentes 2.0 Journal, 2021)
In the last fifty years, the technological development of society has incorporated a series of modifications within the world panorama of all productive sectors. The objective was to analyze the students' concept beyond a number, to explore through a questionnaire their perspective on the use of technological elements in the classroom; teacher's handling the incorporation of said media, and the opinion on its inclusion in the subject of differential calculus, with a view to better academic and teaching performance. A questionnaire used a quantitative approach; this considered the participants' dimensions of assessment and perspective by including technological aspects in the differential calculus classes. When analyzing the impact of technology within the educational process of students, this research applied a questionnaire using closed and open questions. The results showed consistency with previous research on calculation difficulties. However, this study opens an overview of qualitative elements of young people on digital devices focused on the teaching of calculus, which allow creating awareness in teachers to show them a solution proposal to the vital problems existing environments to the course of differential calculus.
Keywords: Differential calculus; Technological Skills; High School